Superstition, religion and the political / Superstição, religião e o político - Despland, Michel (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2011)
<!--[if gte mso 9]> 1024x768 <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> <!--[if gte mso 9]> 1024x768 <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> Abstract/presentation Although a respected researcher of religion in both the European and North American intellectual scene, Michel Despland is to date still little known in Brazilian religion studies circles. Among his several publications, we name but a few: Kant on history and religion: with a translation of Kant's On the failure of all attempted philosophical theodicies (McGill-Queen's University Press, 1973); The education of desire, Plato and the philosophy of religion (University of Toronto Press, 1985); Les hierarchies sont ebranlees, politiques et theologies au XIXe siècle, (Fides, 1998); Comparatisme et Christianisme: questions d'histoire et de methode (L'Harmattan, 2002). In the paper before us, which was presented during the 12th Symposium of the Brazilian Association for the History of Religions (2011, UFJF), Professor Despland starts from the anthropological premise that religion is “something people do”. Drawing on Spinoza’s work, Despland elects the category of “superstition” as the most adequate tool for the analysis of the religious realm, rather than, for instance, “the sacred”. The author’s immediate goal is first to understand Spinoza’s own construal of the religious and political realms in their inter-relatedness – both in conceptual continuity and rupture with the Western/Christian traditions of political theology. He then proceeds to probe historically into the moral and social dimensions of religion as embedded both in its own institutions and in the ever growing third realm of civil society vis-à-vis the state. This discussion, enriched by the contribution of other important writers such as J.-J. Rousseau, A. de Tocqueville, B. Constant and C. Lefort, should serve as a test for his theoretical choices. Despland hopes to have shown, at the end, that a consideration of religion as inevitably rooted in human nature, together with the analysis of the particular historical configuration of the political and religious realms in modern Western civilization, provides us with “a good context for the confrontation with some of the fundamental problems of justice that remain before us today”. Religion as he sees it, therefore, is finally to be understood as psychologically and historically contingent human action. All the same, it takes place over against the irrational-rational background of some philosophically resilient categories: superstition and morality. <!--[if gte mso 9]> 1024x768 <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> Resumo/apresentação Cientista da religião reconhecido e respeitado em ambientes intelectuais da América do Norte e da Europa, Michel Despland é ainda pouco conhecido pela academia brasileira. Entre suas publicações estão, por exemplo: Kant on history and religion: with a translation of Kant's On the failure of all attempted philosophical theodicies (McGill-Queen's University Press, 1973); The education of desire, Plato and the philosophy of religion (University of Toronto Press, 1985); Les hierarchies sont ebranlees, politiques et theologies au XIXe siècle, (Fides, 1998); Comparatisme et Christianisme: questions d'histoire et de methode (L'Harmattan, 2002). No texto ora publicado, apresentado durante o XII Simpósio da Associação Brasileira de História das Religiões (2011, UFJF), o prof. Despland assume a premissa antropológica de que “a religião é algo que as pessoas fazem.” Baseando-se em Espinosa, Despland elege a categoria da “superstição” como um instrumento de análise mais adequado para a análise do religioso do que, por exemplo, a do “sagrado”. O objetivo mais imediato de Despland é primeiramente entender como o próprio Espinosa constrói os âmbitos político e religioso em sua inter-relação, em continuidade e ruptura com as tradições herdadas da teologia política do Ocidente/do cristianismo. A partir daí, ele passa a sondar historiograficamente as dimensões morais e sociais da religião diante do Estado, tanto em suas próprias instituições, quanto no cada vez mais conspícuo terceiro âmbito da sociedade civil. Esta discussão, enriquecida pelas contribuições de outros autores importantes, tais como J.-J. Rousseau, A. de Tocqueville, B. Constant e Lefort, deveria servir como teste para as escolhas teóricas do autor. De fato, Despland espera ter começado a mostrar, no final de seu texto, que uma consideração da religião como inevitavelmente arraigada na natureza humana, junto com a análise da particular configuração histórica dos âmbitos político e religioso na civilização ocidental-moderna, fornece-nos “um bom contexto para a confrontação com alguns dos problemas fundamentais relativos à justiça hoje remanescentes”. A religião, assim como ele a vê, há que ser finalmente entendida como ação humana psicológica e historicamente contingente. Não obstante, ela ocorre diante do pano de fundo irracional-racional de algumas categorias filosoficamente resilientes, a saber: superstição e moralidade.